PERSEPSI MAHASISWA AKUNTANSI TERHADAP MATA KULIAH ETIKA BISNIS DAN PROFESI AKUNTANSI DIPANDANG DARI SEGI GENDER (Studi kasus pada mahasiswa akuntansi yang belum/sudah mengikuti mata kuliah etika bisnis dan profesi akuntansi di STIE Indonesia Banking School) - Putra, Saddam Anazga; Darniaty , Will Andilla (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to find out whether there are differences in the perceptions of accounting students towards business ethics and the accounting profession based on gender and those who have not/have taken courses in business ethics and the accounting profession. The population or objects in this study are active students majoring in accounting at STIE Indonesia Banking School batches of 2019, 2020, 2021 and 2022. The sample selection method used is Convenience Sampling. The results of the study show that: (1) There is no difference in perceptions of accounting students towards business ethics and the accounting profession in terms of gender, and (2) There are differences in perceptions between accounting students who have not and have taken courses in business ethics and the accounting profession.